Tensions Arising from Imposing NPM in Australian Public Universities: A Management Perspective. (May 2015) - Christopher, Joe; Leung, Philomena
Abstract This study seeks to identify the characteristics causing tensions in the move towards a corporate culture in Australian public universities. The findings reveal ongoing structural, competency and behavioral issues contributing to the tensions. Two theoretical propositions have emerged regarding the status of the change process. First, the change to a corporate culture is slow but continuing. Second, universities have accepted that public sector, collegial and corporate cultures have to co‐exist, thus adopting an adapted version of new public management (NPM). These findings provide avenues for further research to confirm both the characteristics and theoretical propositions.